Allah Transendental yang Dinamis: Kristus Pembebas dalam Gustavo Gutierrez dan Aloysius Pieris - Sitorus, Gideon Hasiholan; Simarmata, Rikky Fransiskus (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
This article aims to offer an alternative understanding of the dynamic transcendental God based on the thoughts of Gustavo Gutierrez and Aloysius Pieris. The paradigm of Christ's position as the initiator in liberation and struggle both agree, but in terms of praxis they differ. If Gutierrez rejects intervention from the Almighty with the realization that God has oriented liberation and struggle to every human being, so humans cannot be free from the responsibility to fight for liberation. Pieris contradicts this by prioritizing God's involvement. With an emphasis that God still participates in every liberation and struggle carried out by humans through fellowship in Christ. This involvement is full of prosocial actions so that liberation for the oppressed, marginalized and shackled can be overcome. Through descriptive qualitative research method with literature study and supported by the use of dialectical materialism lens. Data will be obtained through various research results, journals, documents, books and other harmonized information. This article will conclude with a dialogue between Gutierrez and Pieris about the dynamic transcendental God in Jesus Christ who is integrated into the reality of poverty itself. As a result, this paper shows that both Gutierrez and Pieris are calling on all human beings to overcome repressive and even exploitative social structures by prioritizing the realization of the liberative action of the historical and humanist Jesus in the world.